Desacidificação de oleos vegetais por extração liquido-liquido : equilibrio de fases e simulação do processo - Batista, Eduardo Augusto Caldas, 1966- (2002)
Orientadores: Antonio Jose de Almeida Meirelles, Maria Regina Wolf Maciel